A CASE REPORT ON HYPOKALEMIC PARALYSIS AS A RARE PRESENTATION OF KIDNEY INVOLVEMENT IN PRIMARY SJOGREN’S SYNDROME. - Singh, Mritunjay Kumar; A N Rai (Student’s Journal of Health Research Africa, 2024)
Background: Primary Sjogren’s syndrome (pSS) is an autoimmune disorder that primarily affects exocrine glands, commonly causing dry eyes and a dry mouth (sicca component). It can also involve non-exocrine organs, including the skin, lungs, gastrointestinal tract, central and peripheral nervous system, musculoskeletal system, and kidneys. Case presentation: A 21-year-old female presented with sudden quadriparalysis and normal vital signs, ruling out common causes. Clinical examination revealed muscle weakness and absent reflexes. Laboratory findings included low serum potassium, ECG changes indicative of hypokalemia, and non-anion gap metabolic acidosis. A urine spot test confirmed inappropriate renal potassium loss, diagnosing type 1 distal renal tubular acidosis. Positive autoimmune markers led to the diagnosis of primary Sjogren’s syndrome. Treatment with sodium bicarbonate, prednisolone, and oral potassium supplementation resulted in improved muscle power. Conclusion: Kidney involvement in primary Sjogren’s syndrome (pSS) can present uncommonly as hypokalemic paralysis, sometimes occurring before the onset of sicca symptoms. Physicians should consider pSS in patients presenting with hypokalemic paralysis and renal tubular acidosis (RTA), even in the absence of sicca symptoms. Early recognition and appropriate treatment are essential to manage potentially life-threatening hypokalemia and improve renal outcomes.